SISTEM INFORMASI COVID-19 BERBASIS MOBILE DENGAN FRAMEWORK FLUTTER DAN APPLICATION PROGRAMMING INTERFACE (API) - Hermawan Setiawan; Muhammad Novrizal Ghiffari (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
The corona virus (COVID-19) has been happen for long time on the world, recently there is a new variant, namely omicron, which is rapidly spreading throughout the world, especially in Indonesia. The lack and difficulty to creating of spreading data of corona virus, it makes difficulty to know the information of corona virus cases for people especially for people who want doing kinds of trip.  This research uses Information system of Covid-19 to plan the flutter framework and uses APIs to be able to solve these problems. The implementation of Flutter and API can easily collaborate to exchange the data in JSON format, so that data of covid-19 cases and their problems can be handled in the information system.